3D Printing of Highly Stretchable and Tough Hydrogels into Complex, Cellularized Structures. (1st June 2015) - Hong, Sungmin; Sycks, Dalton; Chan, Hon Fai; Lin, Shaoting; Lopez, Gabriel P.; Guilak, Farshid; Leong, Kam W.; Zhao, Xuanhe
<x xml:space="preserve">Abstract</x> A 3D printable and highly stretchable tough hydrogel is developed by combining poly(ethylene glycol) and sodium alginate, which synergize to form a hydrogel tougher than natural cartilage. Encapsulated cells maintain high viability over a 7 d culture period and are highly deformed together with the hydrogel. By adding biocompatible nanoclay, the tough hydrogel is 3D printed in various shapes without requiring support material.